Identifikasi Kandungan Senyawa Antioksidan Ekstrak Daun Bidara (Ziziphus mauritiana Lamk.) Dengan Menggunakan Metode DPPH - La Sakka; Rahmatullah Muin (Journal Syifa Sciences and Clinical Research, 2022)
Bidara is a plant that is known to be rich in antioxidants and is a plant that can withstand extreme temperatures and is able to survive in a rather dry environment. Bidara leaves are included in the type of compound leaves where these compound leaves have branching stalks and on the stem branches there are leaf blades, on one stalk there are more than one leaf blade, a compound leaf is considered to come from a single leaf whose incision is so deep that the the leaves between the nicks are separate from each other and each is a separate little strand. The purpose of this study was to determine the level of antioxidants contained in bidara leaf extract (Ziziphus mauritiana Lamk) using the DPPH method. The method used is the DPPH method (2,2-diphenyl-1-picrylhydrazyl). This test consisted of 4 concentration treatments, namely, 50 ppm, 100 ppm, 150 ppm, and 200 ppm with each comparison of vitamin C with a concentration of 2 ppm, 4 ppm, 6 ppm and 8 ppm. By testing using Uv-Vis Spectrophotometry. The results of this study obtained a linear equation Y = 0.0005x + 0.4172, so the IC50 value is 119.84 (μg/ml), this means that the level of antioxidant activity of bidara leaf extract is moderate.